2020
DOI: 10.1177/1468087420931730
|View full text |Cite
|
Sign up to set email alerts
|

Computational optimization of reactivity controlled compression ignition combustion to achieve high efficiency and clean combustion

Abstract: One of the major limitations of reactivity controlled compression ignition is higher unburned hydrocarbon and carbon monoxide emissions and lower thermal efficiency at part load operating conditions. In the present study, a combined numerical approach using a commercial three-dimensional computational fluid dynamics code CONVERGE along with artificial neural network and genetic algorithm is presented to address the above limitation. A production light-duty diesel engine is modified to run in reactivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…36 Overall, in the RCCI engine, DIT has critical impacts on the combustion characteristics since the start of a direct injection directly controls the rate and time of the air-fuel mixing process. 37 According to numerical research by Mohammadian et al, the influence of injection timing in a singlecylinder heavy-duty RCCI engine was investigated. 38 Their findings showed that by early direct injection at -88 CA ATDC, maximum gross indicated efficiency and also, combustion efficiency was enhanced by nearly 7% and 3.7%, respectively compared to the engine baseline conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Overall, in the RCCI engine, DIT has critical impacts on the combustion characteristics since the start of a direct injection directly controls the rate and time of the air-fuel mixing process. 37 According to numerical research by Mohammadian et al, the influence of injection timing in a singlecylinder heavy-duty RCCI engine was investigated. 38 Their findings showed that by early direct injection at -88 CA ATDC, maximum gross indicated efficiency and also, combustion efficiency was enhanced by nearly 7% and 3.7%, respectively compared to the engine baseline conditions.…”
Section: Introductionmentioning
confidence: 99%
“…36 Overall, in the RCCI engine, DIT has critical impacts on the combustion characteristics since the start of a direct injection directly controls the rate and time of the air-fuel mixing process. 37…”
Section: Introductionmentioning
confidence: 99%
“…25,26 New low temperature combustion (LTC) modes such as HCCI or reactivity controlled compression ignition (RCCI) aim to emit low NOx and low soot concentration thanks to longer ignition delays. [27][28][29] They are nevertheless limited by their MPRR levels due to the rapid auto-ignition of the mixture [30][31][32] and use to exhibit high resonance excitation. 33 Similar to knock in SI engines, the resulting pressure waves represent a source of potential damage for the engine and must be limited and controlled.…”
Section: Introductionmentioning
confidence: 99%
“…In this context of hybridization, several advanced technologies for ICEs are available to reach near-zero CO 2 emissions while allowing for the sustenance of the automotive industry and market [5]. ICE improvements promote benefits in CO 2 [6] and pollutant emissions [7], being the exhaust aftertreatment systems (ATS) key to meet the limits on pollutant emissions in a context of highly dynamic operating conditions [8]. However, the early activation of the catalytic converters is becoming a critical challenge.…”
Section: Introductionmentioning
confidence: 99%